The Influence of Public Accounting Firm Reputation on Audit Report Lag - Wijaya, Melinda; Permatasari, Alya Putri (Formosa Journal of Sustainable Research, 2024)
This research aims to examine and analyze the influence of the reputation of a public accounting firm on audit report lag in companies listed on the Indonesia Stock Exchange in 2022. This research is unique because it uses all sectors of companies listed on the Indonesia Stock Exchange in 2022. The research uses quantitative methods with the sample selection method used is non-probability sampling with purposive sampling technique. This research uses secondary data via the BEI website. The number of samples studied was 504 companies. The results of this research indicate that the reputation of the public accounting firm does not affect audit report lag. The implication of this research is as a means to enrich knowledge and complement literature regarding research on similar topics, then it can be a consideration for companies, auditors and investors in knowing what factors might influence the occurrence of audit report lag